Image Series as Media to Improve Students' Recount Text Writing Skill - Roichan, Fatchur; Sulistyaningsih (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
One of the skills that must be improved in English is writing ability. Improving writing skills requires a creative teacher’s role in carrying out learning. One creative way to improve writing skills, especially the re-count text, is to use a series of images as a learning medium as described in this research. The aim of this research’s to find out whether the use of series of images is effective and can also help students in writing about recount text. This research was conducted on eleventh-grade students at MA Putri Nurul Masyithoh Lumajang in the 2023/2024 academic year. The method used was class action research (CAR). Meanwhile, in analyzing the data resulting from the treatment, the qualitative descriptive analysis method was used. The results of the research show that students' ability to write recount text can be enhanced using a series of pictures as a learning medium.